2005
DOI: 10.4049/jimmunol.175.2.874
|View full text |Cite
|
Sign up to set email alerts
|

CCR2 and CCR6, but Not Endothelial Selectins, Mediate the Accumulation of Immature Dendritic Cells within the Lungs of Mice in Response to Particulate Antigen

Abstract: Dendritic cells (DC) migrate from sites of inflammation to lymph nodes to initiate primary immune responses, but the molecular mechanisms by which DC are replenished in the lungs during ongoing pulmonary inflammation are unknown. To address this question, we analyzed the secondary pulmonary immune response of Ag-primed mice to intratracheal challenge with the particulate T cell-dependent Ag sheep erythrocytes (SRBC). We studied wild-type C57BL/6 mice and syngeneic gene-targeted mice lacking either both endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
83
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 76 publications
(94 reference statements)
10
83
0
1
Order By: Relevance
“…Our use of AF to distinguish macrophages (AF ϩ ) from lung DCs (AF Ϫ ) represents a critical step in our identification process because both cell types express CD11c. This distinction, well described in two prior studies 41,45 and in other infectious and noninfectious models of pulmonary inflammation, 42,[51][52][53]68 permits more specific identification and enumeration of macrophage and DC populations in the lungs of mice. In our model, AF ϩ macrophages, purified by cell sorting, are large cells (with high forward and side scatter) displaying numerous intracytoplasmic vacuoles, some containing cryptococci, consistent with macrophage morphological features (Figure 1).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our use of AF to distinguish macrophages (AF ϩ ) from lung DCs (AF Ϫ ) represents a critical step in our identification process because both cell types express CD11c. This distinction, well described in two prior studies 41,45 and in other infectious and noninfectious models of pulmonary inflammation, 42,[51][52][53]68 permits more specific identification and enumeration of macrophage and DC populations in the lungs of mice. In our model, AF ϩ macrophages, purified by cell sorting, are large cells (with high forward and side scatter) displaying numerous intracytoplasmic vacuoles, some containing cryptococci, consistent with macrophage morphological features (Figure 1).…”
Section: Discussionmentioning
confidence: 84%
“…41 The peripheral blood mononuclear cells were isolated from peripheral blood obtained from the retro-orbital vein of deeply anesthetized mice and processed as previously described. 42 Spleens were excised and leukocytes were dispersed by mincing and mechanical disruption. Bone marrow was harvested by removing the ends from both femurs with a number 10 blade scalpel (after removal of skin and muscle) and flushing the marrow with 2 ml of PBS, using a 3-ml syringe and a 25½-gauge needle, into a sterile 100 ϫ 15-mm dish; leukocytes were dispersed further by mechanical disruption.…”
Section: Tissue Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments in CCR6 Ϫ/Ϫ mice showed a reduced inflammatory response that was partially attributed to decreased pulmonary DC numbers (14). Another study reported a diminished early accumulation of lung DCs in challenged CCR2 Ϫ/Ϫ and CCR6 Ϫ/Ϫ mice (15). Activation and maturation of DCs was severely compromised in CCR2 Ϫ/Ϫ mice (16).…”
mentioning
confidence: 99%
“…Induction of CCR7 on human mDCs by UPM, as we report, supports the results from murine experiments that diesel exhaust particle‐laden DCs translocate to lymph nodes after diesel exhaust particle instillation in to the lungs,31 and is important given that lymph nodes are the primary site for priming of new immune responses in vivo . Decreased expression of CCR2 and CCR6 on mDCs after exposure to UPM in the lungs as indicated by our results may act to release these mDCs from the pulmonary environment, as both are important in chemotaxis of inflammatory DCs in to the lungs 32, 33, 34. However, the resulting effects of down‐regulation of CCR2 and CCR6 on DCs are probably more complex – for example Sato and colleagues have previously shown CCR2 to have a role in migration of Langerhans cells (skin‐resident dendritic cells) to and within lymph nodes, and CCR2 −/− knockout mice to have an exaggerated T helper type 2 immune response to Leishmania major infection 35…”
Section: Discussionmentioning
confidence: 51%